Literatur Review: Pengaruh Profitabilitas Dan Kualitas Audit Terhadap Praktik Manajemen Laba Dipengaruhi Oleh Ukuran Perusahaan BUMN Sebagai Variabel Moderasi - Thresia Agnes Monica Simarmata; Tuti Meutia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Profit management practices, which are often the focus of attention in the context of corporate finance, have a significant impact on public trust and business continuity. This study explores the effect of profitability and audit quality on profit management practices, taking into account the size of state-owned enterprises as a moderation variable. Through an analytical approach, we collected data from the mining sector in the period 2016-2020 which was listed on the Indonesia Stock Exchange. Purposive sampling method is used to determine the research sample. The results showed that profitability has a significant influence on profit management practices, with companies likely to resort to profit management to maintain or increase their profits. On the other hand, audit quality also plays an important role in reducing profit management practices, with auditors from the Big Four Public Accountants considered to have a better ability to detect and prevent adverse practices. However, the size of state-owned enterprises does not necessarily reinforce the relationship between profitability and profit management practices. Large companies tend to have tighter internal controls and better audit quality, which reduces the likelihood of profit management practices. On the other hand, small companies may be more vulnerable to such practices due to limited resources and less effective internal controls.